Profiling and bioinformatics analyses reveal differential expression of circular RNA in tongue cancer revealed by high‐throughput sequencing. Issue 3 (30th September 2018) - Qiu, Xiaoxia; Ke, Xu; Ma, Huaci; Han, Liang; Chen, Qingwen; Zhang, Shu; Da, Peng; Wu, Hao
Abstract: Circular RNAs (circRNA) are special noncoding RNAs. They are widely present, but with unknown functions. Recent studies have shown that many endogenous circRNAs have sponge function to absorb microRNAs (miRNA). They can regulate target gene messenger RNA expression and play important roles in many biological processes. However, expression profile and function of circRNAs in human tongue squamous cell carcinoma (TSCC) have not been reported. High‐throughput sequencing was performed to identify and annotate from three TSCC tissues and adjacent tissues. A separate set ( n  = 20) of human TSCCs and corresponding adjacent tissues were subjected to reverse‐transcription polymerase chain reaction (RT‐PCR) for validation of circRNAs expression profile. Gene Ontology (GO) functional analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and circRNA‐miRNA network analysis were also performed to predict the function of circRNA in TSCC. A total of 12 156 circRNAs were identified and annotated, most of the circRNAs were novel ( n  = 6231) and exonic (62.09%). Statistical analysis revealed 322 differentially expressed (DE) circRNAs. RT‐PCR results showed that circRNA expression in TSCC was higher than that in adjacent tissues. GO functional analysis, KEGG pathway analysis, and circRNA‐miRNA network analysis all showed that circRNAs correlated with tumor development and progression to a certain extent. The current study is the first to systematically characterize and annotate circRNA expression in TSCC, the majority were novel circRNAs. Some host genes of the DE circRNAs were involved in tumor signaling pathway and had complicated correlations with tumor‐relevant miRNAs, indicating that circRNAs might be promoted development and progression of TSCC. Abstract : The current study enriches our knowledge about the eukaryotic transcriptome, fills the research gaps regarding tongue squamous cell carcinoma circular RNAs (circRNAs), provides new ideas for research in tumor development mechanisms and treatment options, and reveals new functions of circRNA molecules.